Orbital Myiasis with Scalp Pediculosis and Buccal Abscess– An Uncommon Presentation - Nidhi Kaeley; Rajeev Mohan Kaushik; Richa Rajput; Renu Dhasmana; Anurag Bhargava (Journal of Clinical and Diagnostic Research, 2017)
We present a case of severe orbital myiasis caused by Osteris ovis, also known as sheep nasal botfly which is an uncommon manifestation of maggot infestation. Our patient was successfully treated with oral as well as topical ivermectin. The experience of ivermectin as an anti-parasitic agent in the treatment of orbital myiasis, although a known entity, is still limited among medical professionals including ophthalmologists. Thus, we would like to highlight the role of oral ivermectin as an anti-parasitic agent in the treatment of orbital myiasis facilitating the removal of maggots; thus, precluding the need for exploratory surgery.